2018
DOI: 10.1186/s12913-018-3613-9
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a precious gift, not to waste”: is routine cross matching necessary in orthopedics surgery? Retrospective study of 699 patients in 9 different procedures

Abstract: BackgroundOrthopedic surgeries are usually associated with excessive blood loss which leads surgeons to overestimate need for blood transfusions and over ordering of blood. The cross matched blood, when not used, leads to the wastage of blood bank resources in terms of time, money and manpower. The objective of this study was to investigate the compliance to previously proposed MSBOS and to provide updated recommendations for all orthopedic procedures.MethodsA retrospective analysis was conducted between 1st J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
2
17
1
Order By: Relevance
“…11 A study conducted in Egypt in 2011 showed a similar overall CT ratio of 3.9 for a wide range of surgical procedures. 4 The mean C/T ratio is also lower than that reported from other studies from Benin (2.2), Nigeria (2.9), and Saudi Arabia (2.96). [12][13][14] A lower C/T ratio indicates better utilization of blood.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…11 A study conducted in Egypt in 2011 showed a similar overall CT ratio of 3.9 for a wide range of surgical procedures. 4 The mean C/T ratio is also lower than that reported from other studies from Benin (2.2), Nigeria (2.9), and Saudi Arabia (2.96). [12][13][14] A lower C/T ratio indicates better utilization of blood.…”
Section: Discussioncontrasting
confidence: 56%
“…19 Other studies have also shown similar results with high C/T ratios but TI within the generally accepted range. 4 The current study is limited by its retrospective design and use of secondary data, which introduces errors like typing errors and missing records. We were unable to determine various other indices of blood utilization due to a lack of detailed records.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations